178. NEOADJUVANT CHEMORADIOTHERAPY VERSUS CHEMOTHERAPY FOR GASTROESOPHAGEAL JUNCTION ADENOCARCINOMA; WHICH IS THE OPTIMAL TREATMENT OPTION?. (24th September 2022) - Farinha, Hugo Teixeira; Zandirad, Eric; Barberà-Carbonell, Beatriz; Demartines, Nicolas; Schäfer, Markus; Mantziari, Styliani
Abstract: Patients with locally advanced gastroesophageal junction (GEJ) adenocarcinoma are treated either with either perioperative chemotherapy (CT) or preoperative radiochemotherapy (RCT) followed by surgery. However, specific selection criteria of one modality over the other still lack, as comparative data for their efficacy remain scarce. The aim of this study was to compare pathologic response and long-term outcomes in GEJ adenocarcinoma patients treated with neoadjuvant RCT versus CT. All patients with locally advanced GEJ adenocarcinoma treated with neoadjuvant treatment (NAT) followed by surgery between 2009 and 2018 in our tertiary referral center were retrospectively analyzed. The x2 or Fisher test were used to compare categorical, and the Mann–Whitney-U test continuous variables. Survival and tumor recurrence were compared with the Kaplan Meier method and log-rank test. Multivariate logistic and Cox regression were performed to identify independent predictors of complete pathological response and long-term survival. Among the 94 included patients, 67 (71.2%) received RCT and 27 CT. Complete pathologic response was more frequent in RCT patients (13.4% vs 7.4%, p = 0.009), who had a trend to better lymph node control (ypN0) (55.2% vs 33.3%; p = 0.057), but similar rates of R0 resection (66.7% vs 72.1% CT, p = 0.628). RCT patients had more postoperative cardiovascular complications (35.8% vs 11.1%; p = 0.017). Long-term overall and disease-free survival were similar in the two groups (5-year OS 61.1% RCT vs 75.7% CT, p = 0.259; 5-year DFS 33.5% RCT vs 22.8% CT; p = 0.763). NAT type was not independently associated with pathologic response nor long-term survival. Patients with locally advanced GEJ adenocarcinoma demonstrated higher rates of complete pathologic response after neoadjuvant RCT than CT and a trend to superior locoregional lymph node sterilization, although this did not translate in a significant survival or recurrence benefit.